Society's Entrepreneurship During The Pandemic Through The Water Hyacinth Handicraft in The Village of Walahar Klari Distric of West Java - Eliza Rahmah Prahestiwi; Ade Sadikin; Lip Saripah (Universitas Negeri Padang, 2021)
This research was motivated by the problem of the impact of the Covid 19 pandemic which resulted in many people being unemployed and the large number of water hyacinth plants were only considered garbage in Walahar. This condition is seen as an opportunity and a challenge in exploiting the potential of the region. Efforts to overcome this are by opening job vacancies, making entrepreneurial training from raw materials for water hyacinth waste. The objectives of this study are to: a). Obtaining information about increasing community entrepreneurship during the Covid 19 pandemic through water hyacinth crafts. b). To find out what the supporting and inhibiting factors are. c). To find out the results of increasing community entrepreneurship during the Covid 19 pandemic through water hyacinth handicrafts (case study in Desa Walahar Kec. Klari Kab. Karawang Prov. Jawa Barat). To answer the formulation of research problems that have been formulated, the author uses a qualitative approach with the case study method. To explain the phenomena that appear in the field. The research sources are: a). Sources of information, namely the chairman and owner of water hyacinth handicrafts UKM Kab. Karawang